Israeli Identity in Crisis: Cinematic Representations of the 1982 Lebanon War - Blab, Danielle E. (Université d'Ottawa / University of Ottawa, 2012)
This thesis engages with the relationship between national identity, security-based narratives, and foreign policy. It focuses on the 1982 Lebanon War as the most controversial in Israel's history because it violated the Israeli societal norm of only fighting wars of self-defence (when there is no alternative to war). Through an examination of Israeli films about the 1982 war – Ricochets, Time for Cherries, Cup Final, Waltz with Bashir and Lebanon – this thesis studies the identity crisis experienced by Israelis after the invasion of Lebanon and the coping mechanisms that helped Israeli society reconcile the war with the security-based narratives that inform collective identity in Israel.

Cette thèse a pour objet la relation entre l’identité nationale, les récits sécuritaires et la politique étrangère. Elle se base sur la Guerre du Liban de 1982 en tant que guerre la plus controversée des guerres israéliennes en raison de sa contradiction avec la norme israélienne de seulement mener des guerres de légitime défense (à savoir lorsqu'il n'y a aucun autre recours que la guerre). À travers un examen des films israéliens qui traitent de la guerre de 1982 – Ricochets, Time for Cherries, Cup Final, Waltz with Bashir et Lebanon – cette thèse discute de la crise identitaire vécue par les Israéliens à la suite de l'invasion du Liban et s’intéresse aux stratégies d'adaptation qui ont aidé la société israélienne à réconcilier la guerre avec les récits sécuritaires qui font partie de la construction de l'identité collective israélienne.
Keywords: Israel; Lebanon; Film Analysis; Identity; Security Narratives; Foreign Policy; Militarism; 1982 Lebanon War; Israeli Identity